Efekti žučnih soli i himekromona na recidiv žučnih kamenaca kod odraslih pacijenata nakon laparoskopske holecistolitotomije - Salikhova, Tursunay; Kuramyssov, Yerkin; Zhirgalieva, Laura; Salikhov, Arsen; Rakhmatullin, Yussupzhan (Medicinski časopis, 2025)
Given the priority of organ preservation in modern surgery, optimising postoperative treatment, particularly following the removal of gallstones while preserving the gallbladder, is highly relevant. This study aimed to evaluate the effectiveness of comprehensive medical support in restoring gallbladder functionality and preventing the recurrence of gallstone disease (GSD) after organ-preserving cholecystolithotomy. The study was retrospective in design, covering the period from 2018 to 2024, and was conducted at a medical centre in Almaty, Kazakhstan, a country with a high prevalence of GSD. It included 115 patients aged 18 to 65 years who underwent cholecystolithotomy. Of these, 98 patients remained under dynamic observation for a specified follow-up period. Postoperative pharmacotherapy comprised ursodeoxycholic and taurodeoxycholic acids, hymecromone, broad-spectrum antibiotics to prevent infectious complications, analgesics for pain management, antispasmodics to relieve biliary tract spasms, and other medications, with dosages adjusted individually based on the patients’ conditions. To monitor gallbladder status and evaluate treatment effectiveness, ultrasound examinations (US) were performed preoperatively, postoperatively, and periodically during the observation period. The comprehensive assessment also included a general urine analysis conducted before and after surgery. The results of US indicated that complex drug therapy facilitated the normalisation of gallbladder wall size and thickness, as well as improved contractile function. Long-term follow-up revealed that 98.6% of patients retained normal gallbladder contractility, the recurrence rate of cholelithiasis was only 0.07%, and sludge formation was observed in 8.9% of cases. In conclusion, complex pharmacotherapy following cholecystolithotomy with gallbladder preservation is an effective approach for restoring organ function, preventing recurrent stone formation, and enhancing patients’ quality of life. The data obtained from this study can inform the development of clinical guidelines for the postoperative management of patients following gallstone removal with organ preservation.